Risiko Kesehatan Mental dan Peran Dedikasi - Zainuddin, M Said; Usman, Arifuddin; Zakaria, Ahmad (e-SPORT: Jurnal Pendidikan Jasmani, Kesehatan dan Rekreasi, 2025)
This study aims to analyze the mental health impacts of esports involvement, focusing on the psychological characteristics of professional players compared to recreational players. A mixed-methods approach was used, combining qualitative and quantitative research, with in-depth interviews and surveys used to collect data on players' anxiety, depression, and motivation. The results indicate that player motivation falls into two categories: intrinsic, related to personal satisfaction and skill development, and extrinsic, involving financial rewards and social recognition. These findings suggest that intrinsically motivated players tend to have better mental well-being, while reliance on extrinsic motivation can increase the risk of stress and anxiety. Furthermore, involvement in the esports community can provide significant social support, although there are also mental health risks due to competitive pressure. The conclusions of this study emphasize the importance of understanding both sides of the impact of esports on mental health, as well as the need for more effective support strategies for players to reduce stigma and improve their well-being in an increasingly digital world.   Keywords: Psychological Impact of Esports, Mental Health, Motivation